(untitled) (Altre Modernità, 2024)
2014 saw the beginning of the collaboration between Altre modernità and the Società Italiana delle Letterate (SIL), which Serena Guarracino has coordinated over the course of this decade with great wisdom and sensibility, relaunching issue after issue the debate of an association that, since its inception in 1996, has contributed to the formation of feminist literary criticism in Italy, spanning diverse disciplines and knowledges. In succeeding Serena Guarracino today, I would like to thank her and Altre modernità because it has been a work whose constant commitment has permitted the development of valuable reflections and contributions perspective and innovative positioning. Many are the themes that have been addressed in this section: from the first essays on the ’personaggia’ in 2014,—now recognized by the Accademia della Crusca and in the public domain, and considered since its inception as a critical figure of irreducible freedom in literature, cinema and theatre—, to the rereading of SIL’s collective critical contributions in what Serena Guarracino has suggestively called “reviews from the future”, to the collaboration with the ‘Lingua Madre’ literary competition. This issue offers a re-reading of the volume Comiche! Anche le donne ridono, published in 2020— a bold endeavour amidst the pandemic, when there appeared to be nothing to laugh about. The volume collects and reworks materials from SIL’s residential summer seminar held in Viterbo in 2018, which Emma Scaricamazza then compares with the writing of Margherita Giacobino and her Un’americana a Parigi, published under the pseudonym of Elinor Rigby, delving into its comic and parodic aspects. We will thus follow the path paved by Serena Guarracino and SIL, wishing both of them and Altre modernità much future criticism. Anche le donne ridono: da Le comiche a Margherita Giacobino di Emma Scaricamazza (Università degli Studi Roma Tre)